ANALYSE DES PROPOS TENUS PAR DES REFUGIÉS MINEURS NON ACCOMPAGNÉS DANS DES TEXTES IDENTITAIRES. NOUVEAUX VECTEURS D’INCLUSION ? - Gatsi, Giota (Neofilolog, 2019)
According to EKKA (National Center of Social Solidarity), in 2016, almost 5000 unaccompanied minor refugees were registered in Greece. Our research is part of a research for new methodological tools enabling language teachers to adapt their teaching to the needs of these new learners, in particular by exploiting their cultural and linguistic capital. One of these tools is the "identity text" which, according to Cummins (2006), is a reflection of the author's identity at some point in his/her biography. The hypotheses of our research are that the production of identity texts by unaccompanied minor refugees can reinforce (H1) their self-esteem, (H2) their motivation for learning new languages in school and (H3) the development of skills that could lead to better in-tegration (affective, linguistic, cultural and socio-cultural) within the host country's school system. These hypotheses are confirmed by the results of cross-content analysis of a collection of identity texts pro-duced online (on Facebook) in 2016-2017 by 30 unaccompanied minor refugees of Syrian, Afghan and Pakistani origin, aged between 14 to 18 years old. It appears that our three hypotheses are validated to a significant extent. These findings may be an incentive for language teachers, but perhaps also for the actors of Formal and Non Formal education to observe and anchor the linguistic and cultural skills of newly arrived refugees, so that they find their place more easily in a welcoming society.